Impact of COVID-19 on radiology education in Europe: a survey by the ESR Radiology Trainees Forum (RTF) - European Society of Radiology (ESR) (SpringerOpen, 2021)
Abstract Background The ongoing COVID-19 pandemic has significantly affected radiology services around the globe. The impact of the crisis on radiology education in Europe has yet to be determined, in order to identify measures to achieve optimal training of radiologists during pandemics. The aim of this survey was to evaluate the impact of the pandemic on young radiologist members of the European Society of Radiology (ESR). Methods A survey consisting of 28 questions was developed and distributed using SurveyMonkey to all ESR European radiologist members in training. The survey sought to collect information on three main themes, ‘demographics’, ‘training level’ and ‘effects of COVID-19’. The responses were statistically analysed with the use of R programming using descriptive statistics. Results A total of 249 responses from 34 countries were collected. Specific training on COVID-19 was not offered to 52.2% (130) of the participants. A total of 196 participants were not redeployed to other specialities but only 46.2% of institutions allowed residents to work from home. E-learning was offered at 43% of the departments and most participants (86.2%) were not allowed to switch from clinical work to research. A minority (n = 13) were suspended with (30.8%) or without salary (38.5%) or were forced to take vacation/yearly holiday leave (7.7%) or sick leave (23%). Almost half of the participants did not have access to personal protective equipment and a minority of them had their financial status affected. Conclusions The ongoing SARS-CoV-2 outbreak has significantly affected all aspects of postgraduate radiology training across the ESR member countries.